PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ADHI KARYA (PERSERO) PROYEK PEMBANGUNAN UNIVERSITAS NEGERI PADANG - Fitriadi, Yohan (RC-INSTITUT, 2018)
This study aims to analyze the style of leadership, Organizational Culture and Job Satisfaction on employee performance at PT. Adhi karya (Persero) tbk Development State University of  Padang Project, either partially or simultaneously. The method used in the sampling is purposive sampling based on the consideration to adjust the criteria to improve the accuracy of the research sample. The analysis method used is multiple linear regression with significant level (α) of 0.05. The results of this study indicate that the style of leadership has a significant effect on employee performance, with a significant value of 0.000 less than 0.05. Organizational culture has no significant effect on employee performance, with significant value 0,154 less than 0,05. The variable of job satisfaction is not significantly influenced to work performance, with significant value 0,110 less than 0,05. Leadership style, organizational culture and job satisfaction simultaneously influence consumer purchase decisions, with a significant value of 0.000 less than 0.05.   Keywords: Leadership style, Organizational Culture, Job Satisfaction and Employee Performance